Implementation of Pancasila and Law Enforcement Compliance with the Professional Code of Ethics - Gusagis Khomanur Ngaziz (Law Review, 2022)
This legal research seeks to answer three research problems, and by using a qualitative descriptive method. The following conclusions are obtained: First, the code of ethics of the legal profession in Indonesia contains the noble values of Pancasila. In every code of ethics of the legal profession in Indonesia, it always emphasizes that law enforcers must fear God Almighty and always uphold justice. Second, every law enforcer in Indonesia has been given education to live up to the noble values of Pancasila. Having good knowledge of Pancasila is very important because in accordance with their oaths and promises they must uphold the 1945 Constitution which contains the noble values of Pancasila. Third, every law enforcer who has practiced the noble values of Pancasila will become a person who fears God Almighty. Having high integrity, honesty, fairness, responsibility, discipline, and high professionalism, as well as a higher level of compliance with the code of ethics.